Determinación del costo de los productos de la panadería y repostería a través de un sistema de costos por órdenes de producción en la empresa “Jhon Pan” en la ciudad de Villavicencio (2021)
The JHONPAN Bakery is a commercial establishment that has been operating for twelve years offering to the community products of the bakery industry, without having an appropriate system that allows it to determine the manufacturing cost of its products, and therefore, to calculate more accurately the amount of its income and the monthly sales volume in terms of units. Likewise, the lack of an appropriate costing system for the business has meant that its owners and directors do not know if the profit margin of the operation and the profitability are correct, as well as the individual sales price. Therefore, in this research work, it were analyzed the strategic framework of JHONPAN Bakery, the production process, unit costs by type of product such as raw materials, manufacturing overhead and labor were analyzed also. On the other hand, the different cost theories and costing systems were analyzed in order to determine which is the most convenient costing system for the business. In summary, it was determined through the research that the costing system that provides the best advantages to the JHONPAN Bakery is the production order costing system.